PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL DAN UKURAN KANTOR AKUNTAN PUBLIK TERHADAP INTEGRITAS LAPORAN KEUANGAN - Julius Yoga Inganta Sinulingga (2020)
This research was conducted to examine the influence of institutional ownership, managerial ownership and the size of the Public Accounting Firm on the integrity of financial statements. In this study the integrity of financial statements is measured using the Modified Jones Model, institutional ownership and managerial ownership are measured by the ratio of share ownership and the size of Public Accounting Firm with dummy variables. The population in this study are state-owned companies (SOEs) listed on the Indonesia Stock Exchange for the period of 2015-2018. Samples were selected using the purposive sampling method and 59 data samples were collected. The hypothesis in this study was tested using Multiple Linear Analysis with SPSS version 25 and a significance level of 5% (0.05). The results of this study are: 1) institutional ownership has no significant effect on the integrity of the financial statements; 2) managerial ownership has a negative and significant effect on the integrity of financial statements; 3) the size of Public Accounting Firm has a positive and significant influence the integrity of financial statements.